Sociologies du travail: quarante ans après - Bernoux, Philippe (Relations industrielles / Industrial Relations, 2002)
The article reviews the book, "Sociologies du travail : quarante ans après," edited by Amélie Pouchet.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; History; Labor; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social aspects